Proyeksi Penurunan Emisi CO2 melalui Konversi Kendaraan Konvensional ke Kendaraan Listrik di Jawa Barat - Mochamad Dinar (Journal PEP Bandung, 2025)
The increasing economic growth will have an impact on increasing population mobility. The increase in population mobility, which generally still uses private vehicles both cars and motorcycles, results in an increase in CO2 emissions globally. This has an impact on climate change which has the potential to cause negative externalities that need to be followed up immediately. There are several efforts to reduce CO2 emissions in the transportation sector ranging from vehicle restrictions, improving public transportation facilities, and electrifying conventional vehicles. Based on several studies that have been conducted, it shows that vehicle electrification is the most appropriate step at this time to be able to immediately reduce CO2 emissions. Electric vehicles have been proven to produce lower CO2 emissions than conventional vehicles. Therefore, this study calculates CO2 emissions through the conversion of conventional vehicles to electric vehicles in West Java Province, which is the province with the largest population and vehicles in Indonesia. Based on the calculations carried out in this study using the 2006 IPCC method approach, the results showed a lower emission reduction of around 50% through the conversion of conventional vehicles to electric vehicles.